1982
DOI: 10.2307/3586633
|View full text |Cite
|
Sign up to set email alerts
|

Teaching ESL Students to Read and Write Experimental-Research Papers

Abstract: Reading and writing experimental-research papers is important to academic and processional success in the sciences and social sciences, and is becoming increasingly important in the humanities. Few ESL teachers, however, feel comfortable teaching ESL students to read and write such papers. This paper presents both a discussion of experimental-research paper organization and a method for teaching reading and writing of experimental-research articles to ESL students. ESL teachers are advised to teach students to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
5

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 5 publications
0
31
0
5
Order By: Relevance
“…Until recently, there have been few if any ESL texts which deal with how to read and write such papers (Hill ~ ~ 1982).…”
Section: (Est) •mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, there have been few if any ESL texts which deal with how to read and write such papers (Hill ~ ~ 1982).…”
Section: (Est) •mentioning
confidence: 99%
“…The need for EST materials concerned with the scientific paper As Hill, Soppelsa and West (1982) observe, the ability to read and write experimental-research papers is important for success in the sciences. It has also been observed that science students exhibit a clear preference for technical, subjectrelated materials to be used in ESL classes.…”
Section: (Est) •mentioning
confidence: 99%
“…Other authors have made the same point as Swales (e.g. Cook & Meyer, 1988;Hill, Soppelsa, & West, 1982) although it has to be noted that some authors are rather critical of this so-called 'genreist' approach. These opponents argue that students should not be coerced into using stilted forms of text (for an overview of this discussion, see Purcell-Gates, Duke, & Martineau, 2007).…”
Section: Genre Analysismentioning
confidence: 90%
“…Global structure, in contrast, has received less attention. After Hill, Soppelsa, and West's (1982) description of the general arrangement of experimental-research articles, investigations concerning this structural level have been few and somewhat isolated (e.g., Posteguillo, 1999;Ruiying & Allison, 2004;Sollaci & Pereira, 2004). It seems that only recently has macrostructure started to be examined on a more regular basis (see Aragão, 2011aAragão, , 2011bAragão, , 2015Lin & Evans, 2012).…”
Section: Introductionmentioning
confidence: 99%